Implementation Of Hypothesis Testing In Quantitative Research: A Case Study Of The Undergraduate Information Systems Program, Faculty Of Computer Science, Universitas Putra Indonesia Yptk Padang - Pinta Medina; Beni Harma; Susriyati; Devi Syukri Azhari (Jurnal Teknik dan Teknologi Tepat Guna, 2026)
Hypothesis testing is a crucial stage in quantitative research to examine the validity of preliminary assumptions based on empirical data. In higher education, particularly in the Undergraduate Information Systems Study Program, Faculty of Computer Science, Universitas Putra Indonesia YPTK Padang, hypothesis testing plays an important role in producing accurate information regarding relationships and influences among variables related to learning processes, information technology utilization, and students’ academic achievement. However, limited student understanding of hypothesis testing often leads to less optimal research outcomes. This study employed a quantitative approach using a case study method. Data were collected through questionnaires distributed to students as respondents and analyzed using inferential statistical techniques, including validity and reliability testing, regression analysis, and hypothesis testing through t-tests and F-tests with the assistance of statistical software. The results revealed that the proposed hypothesis was accepted, with significance values lower than the error level (α = 0.05), leading to the acceptance of H₁ and rejection of H₀. These findings confirm significant relationships and influences among the investigated variables, contributing to improved learning quality and academic performance. In conclusion, proper application of hypothesis testing enhances the validity, reliability, and credibility of student research. Strengthening students’ understanding of hypothesis testing concepts and techniques is essential to support the quality of academic research in the Undergraduate Information Systems Study Program